Prosciara Frey (Diptera, Sciaridae) revisited: Remarks on classification and description of nineteen new Indomalayan species - Vilkamaa, Pekka (Zootaxa, 2026)
The following nineteen species of Prosciara Frey (Diptera, Sciaridae) from the Indomalayan region are newly described and illustrated: Prosciara aduncula sp. nov. (Thailand), P. aequilobata sp. nov. (Brunei), P. anguina sp. nov. (Nepal), P. bulbacea sp. nov. (Thailand), P. calvata sp. nov. (Thailand), P. clypeata sp. nov. (Thailand), P. cymosa sp. nov. (Brunei), P. devexa sp. nov. (Thailand), P. furculigera sp. nov. (India), P. horrifera sp. nov. (Thailand), P. mediana sp. nov. (Thailand), P. microceps sp. nov. (Thailand), P. minacis sp. nov. (Nepal), P. nudimana sp. nov. (Thailand), P. operta sp. nov. (Thailand), P. perfidiosa sp. nov. (Taiwan), P. pinnifera sp. nov. (Malaysia), P. substricta sp. nov. (Thailand) and P. tenebrosa sp. nov. (Thailand). Including the newly described ones, 114 species of Prosciara are known from the Indomalayan region. The classification of Prosciara and related taxa is discussed.